Assessment of crown dimensions of primary teeth in a selected sample of Indian children - An odontometric study - G. Kavyashree; K. L. Girish Babu (Wolters Kluwer Medknow Publications, 2023)
Introduction: The size and shape of the tooth are important sources of information for anthropology, forensic odontology, and clinical dentistry. Different populations, and even individuals within the same population, may have variations in the odontometric characteristics of their teeth, which limits the applicability of the data across groups. Aim: To establish the normal odontometric data of primary teeth and examine the sexual dimorphism and its usefulness as a tool to identify the sex among young children. Materials and Methods: This cross-sectional study involved 150 children aged 3-5 years. The parents of the selected children were informed about the procedure protocol of the study and their written consent was obtained. The negative replica of the maxillary and mandibular teeth was obtained and dental casts were prepared. The mesiodistal, buccolingual, and crown height dimensions of each tooth were measured with a digital Vernier caliper. Two independent examiners measured each tooth's dimensions three times, and the mean was analyzed. Results and Discussion: There was no significant difference between the teeth in the right and left quadrants. Males had larger odontometric dimensions than females. The sex of children based on odontometrics of primary teeth crowns could be determined with an accuracy of 98%, 72%, and 86% using mesiodistal, buccolingual, and crown height dimensions, respectively. Conclusions: There was a clear sexual dimorphism of the primary teeth. The odontometrics can be used as a low-cost and alternative tool for sex identification among children.